A rádio na prestação de serviços à comunidade: o caso do programa Radar Noticioso da Rádio Metropolitana AM 1070 de Mogi das Cruzes - Schiavi, Marilei José (2012)
This research aims to study the radio as a way to serve the community. For this purpose it analyzed a specific radio show that is on the air for almost fifty years and leads the score of audience, every morning, in the region called Alto Tietê. This radio-news show is called Radar Noticioso of the radio Metropolitana AM 1070 in the city of Mogi das Cruzes. The Metropolitana radio covers more than eleven cities, with over 2.5 million inhabitants. The choice of this program as an object of this research was due the longevity of it almost fifty years, the credibility that grew along this years inside the community. Because of it, the radio-news show was featured in the flow of the demand on the people who listen to it that seek an environment that support them in solving their personal and collective problems. The study is presented in three parts. First the history of the radio, since it origins to present. The second part focuses on the experience of radio in building citizenship a successful experience of Radio Metropolitana de Mogi das Cruzes. The results show that the Metropolitan Radio listener recognize it as a provider of services to the community, and among the programs of this radio, is highlighted in the speech of the interviewees. The Radar Noticioso, the news program, listens to the appeals from listeners and seeks solutions between those responsible for political actions within the region where it reaches. We conclude that the radio, through that program, support the population in providing social service to the community